Istanbul, Türkei. Von Babylon nach Istanbul. Erste Einblicke in die Babylon Sammlung des Istanbuler Archäologischen Museums (2017–2019) - Schachner, Andreas (e-Forschungsberichte des DAI, 2020)
For two years an interdisciplinary team has been dedicated to the evaluation of the small part of the finds of the German Oriental Society‘s excavations in Babylon before and during the First World War, which is store in the Archaeological Museums in Istanbul. Despite the fact that in most cases the findspots are almost impossible to clarify, the archaeological artefacts themselves provide unique insights into the chronological development and the cultural diversity of one of the most important cities of the Ancient Near East; especially since the material culture in its chronological and cultural diversity has so far contributed only very little to Babylon‘s interpretation.